Status Hukum Anak dari Perkawinan Berbeda Kewarganegaraan Perbandingan Hukum Perdata dan Hukum Islam - Jalaludin, Diding; Deni Kamaludin Yusup; Tatang Astarudin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The purpose of this research is to analyse the legal status of children born from marriages of different nationalities in the perspective of Indonesian Civil Law and Islamic Law. This research is important because children born from mixed marriages are entitled to protection of their legal status in order to maintain the continuity of life, legal position and civil interests. The research method used is normative juridical legal research with qualitative data types in the form of secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials relevant to the topic of this research and data collection techniques using library research or literature studies with legal material analysis techniques using descriptive analysis methods. The results of this study state that the law of marriage between different nationalities in the perspective of Indonesian civil law and Islamic law raises problems with the law of marriage itself as well as the legal status, civil rights and citizenship rights of children. In the perspective of Indonesian civil law and Islamic law, the law of marriage of different nationalities is a valid marriage and the legal status of the child is a legitimate child, the civil rights of children from marriages of different nationalities are the same as children in general and the legal status of the child's citizenship as an Indonesian citizen follows the citizenship of the father or mother who is an Indonesian citizen and can also have dual citizenship until he is 18 years old or married, after which the child must declare choosing one of his citizenship.